Loss in translation: a contrastive genre study of original and localised non-profit US websites - Miguel A. Jiménez-Crespo (JoSTrans: The Journal of Specialised Translation)
The notion of 'translation loss' has been at the core of numerous publications and theorisations in Translation Studies (Nord 2011). This paper revisits this notion in the light of new dynamic digital genres with open hypertextual structures that are constantly enlarged and updated. The localisation of these websites, understood as a process constrained by finite time and financial resources, normally entails deciding or prioritising which sections or blocks will appear in the localisation and which will not. These strategies have an impact in the configuration of the localised websites and their potential impact on the communities they address. The present genre-based study analyses from a descriptive perspective a representative corpus of the 'non-profit website' genre in the United States and contrasts non-translated original websites to their Spanish localised versions. After a descriptive study of this digital genre, a contrastive superstructural study shows the differences between these two distinct textual populations in terms of 'localisation loss,' or the chances of sections of the source website not being localised. This analysis sheds some light on the perspective of producers and translation commissioners on the genre, and on the potential differences between non-translated and translated digital genres.